Habitat Selection of Neotropical Otter (Lontra longicaudis) (Carnívora: Mustelidae) in the Iberá Natural Reserve, Argentina - Pocasangre-Orellana, Xochilt (2018)
Habitat selection of the neotropical otter (Lontra longicaudis) was evaluated in the Iberá Natural Reserve, province of Corrientes, Argentina, from July to November 2014. We sampled 99 segments of 300 m in length, which were located in the Iberá lagoon, the Paraná lagoon, and the Arroyo Carambola. Each segment was visited to create detection / non-detection histories of the neotropical otter. Environmental attributes were measured, such as environment type, vegetation cover, and influence of alligator (Caiman latirostris and C. yacare). These attributes were used to create occupation models. The neotropical otter selected the Iberá lagoon over the other environments analyzed. No type of vegetation cover was selected over another, and the influence of alligator did not seem to condition the use of the space of neotropical otter in the sites sampled.